THE EFFECT OF PRICE PERCEPTION AND PRODUCT QUALITY ON PURCHASE DECISION (RESEARCH ON BRAND NEW IPHONE) - Naila, Lala (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Price and Quality of Product are both huge factor to make customer decide and make a purchase decision, the purpose of this research is to find the effect of Price Perception and Product Quality on Purchase decision when purchasing an iPhone product. This research used Questionnaire as a method to get respondents on this Quantitative Research. This study found there is a relationship between price perception and product quality towards purchase decision, and also found that the dominant variable that effecting the purchase decision is Product Quality. This may be occurred because people tend to choose the mobile phone that having a good quality of product, and more aware with it rather than the price they offered.Keywords: Price perception, product quality, purchase decision, iPhone.